Pembelajaran IPA Berbasis Lingkungan Pesisir untuk Meningkatkan Literasi Sains Siswa Madrasah Tsanawiyah - Dede Kusnandar (CV. Intake Pustaka, 2026)
Science learning in junior secondary schools continues to face challenges in fostering students’ scientific literacy, particularly in rural and coastal areas rich in environmental potentials but under-utilised as learning resources. This study aims to develop a science learning model based on coastal environments tailored to the local context of Madrasah Tsanawiyah (MTs) Legokjawa, Cimerak Subdistrict, Pangandaran Regency, and to analyse its effect on students’ scientific literacy. The research employed a Research & Development (R&D) approach encompassing needs analysis, model design, expert validation, limited trial, and final revision. The subjects were grade VIII students of MTs Legokjawa in the 2025/2026 academic year. Instruments included a scientific literacy test, student activity observation sheet, and student questionnaire. The results indicate that the developed model is feasible (average expert validation score 88.5 %) and significantly increased students’ scientific literacy by 24.6 %. These findings suggest that coastal-based contextual learning enhances conceptual understanding, scientific process skills, and environmental awareness among students. The implications for practice include contextual learning implementation in coastal schools and reinforcement of the Merdeka Belajar curriculum.